Seawater carbonate chemistry and the effect of ocean acidification on olfactory behaviour and physiology of Hemigrapsus oregonensis - Khodikian, Elissa; Roggatz, Christina C; Yoon, Gwangseok R; Porteus, Cosima S (PANGAEA, 2025)
This study identified the changes in olfactory behaviour and physiology with exposure to acute, static, and fluctuating CO2 in the yellow shore crab, Hemigrapsus oregonensis. Crabs were collected from Bamfield British Columbia, Canada and brought in for laboratory testing at Bamfield Marine Sciences Centre. Olfactory behavioural testing determined changes in preference to an odorant and time to reach an odorant with exposure to ocean acidification. Olfactory physiology was investigated by determining changes in receptor protein expression and changes in olfactory sensory neuron proliferation.
Keywords: climate change; crustacean; hypercapnia; Laboratory experiment